MODERN MANAGEMENT SOLUTIONS IN LOGISTICS MANAGEMENT - BOKOVETS, Viktoria; SHVARTS, Iryna; BEZSMERTNA, Oksana; VEROVKIN, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Logistics management is a key component of modern enterprise management, especially in the context of globalization and dynamic market development. Modern challenges, such as increasing competition, the need to reduce costs, improve customer service and the integration of digital technologies, necessitate the development of effective management solutions. These solutions not only contribute to the optimization of logistics processes, but also ensure the sustainability of the business and its competitiveness. In this context, the study of modern approaches to logistics management is of practical importance for increasing the efficiency of enterprises and their adaptation to rapid changes in the market.Despite the significant attention paid to logistics management in the scientific literature, there are still a number of unresolved issues that require further research. In particular, the mechanisms for adapting logistics systems to digital transformations, integrating artificial intelligence and automation into management processes have not been sufficiently disclosed. The issue of developing sustainable logistics management models that take into account economic, environmental and social aspects also remains relevant. In addition, the practical aspects of implementing innovative approaches in the logistics of small and medium-sized businesses, which face limited resources for scaling and modernization, require additional analysis.The article considers modern approaches to making management decisions in logistics management that ensure the competitiveness and efficiency of enterprises. Emphasis is placed on the implementation of innovative technologies, such as process automation, Big Data, and the use of artificial intelligence to optimize logistics chains. Key challenges are analyzed, in particular the need to adapt to rapidly changing market conditions and globalization trends. Prospects for the development of logistics management through the integration of modern management practices and tools are identified. Practical recommendations are proposed for improving management processes that contribute to reducing costs and increasing the level of customer service.
Keywords: logistics management; management decisions; process optimization; strategic planning; cost reduction; service level; modern technologies